Measurement of the Λb polarization and angular parameters in Λb →j /ψ Λ decays from pp collisions at s =7 and 8 TeV MEASUREMENT of the Λb POLARIZATION ⋯ A. M. SIRUNYAN et al. - Sirunyan, A. M.; Tumasyan, A. R.; Adam, Wolfgang; Ambrogi, Federico; Asilar, Ece; Md. Ali, Mohd. Adli (American Physical Society, 2018)
An analysis of the bottom baryon decay Λb → J=ψð→ μþμ−ÞΛð→ pπ−Þ is performed to measure the Λb polarization and three angular parameters in data from pp collisions at ffiffi s p ¼ 7 and 8 TeV, collected by the CMS experiment at the Large Hadron Collider. The Λb polarization is measured to be 0.00 0.06ðstatÞ 0.06ðsystÞ and the parity-violating asymmetry parameter is determined to be 0.14 0.14ðstatÞ 0.10ðsystÞ. The measurements are compared to various theoretical predictions, including those from perturbative quantum chromodynamics.